ENHANCEMENT OF PHOTOSYNTHETIC RATE THROUGH PHOTOPERIOD USING LED IN CUCUMBER (Cucumis Sativus) - Mayorazaki, Feby; Esyanti, Rizkita Rachmi; Faizal, Ahmad (MATTER: International Journal of Science and Technology, 2015)
Previous studies have demonstrated that photosynthetic rate in plants could be enhanced by manipulating their photoperiods. Therefore the aim of this study was to investigate the effect of day length using combination of red (R), blue (B) and yellow (Y) light provided by LED (lightemitting diode) on photosynthetic rate of cucumbers. Two cucumber cultivars (Mercy and KE- 27187) were incubated under 8 h, 12 h, and 16 h photoperiod using a composition of RBY-LED light (80:10:10) and HPS + TLD lamps (as a control) inside growth chambers for 28 days. We obtained that 16 h photoperiod resulted in the best quality of plants, in terms of growth rate, sugar content, chlorophyll content, and mass balance among the treatments. However, LEDincubated plants consumed energy less efficiently compared to control plants. This indicates that precise LED specifications should be re-adjusted to maximize energy efficiency for plant production.